Pengamatan Hilal Siang Hari di OIF Cabang Barus - Muhammad Dimas Firdaus; Hariyadi Putraga; Muhammad Hidayat; Arwin Juli Rakhmadi (Islamic Astronomy Department, Sharia and Law Faculty, 2022)
Crescent observation as one of the practices carried out within the scope of falak science has an escalation in methods to adapt the development of science and technology. The development of crescent observation method has an impact on the observation time. In the past, observing crescent only focused when the sun had set, but now observing crescent can be done since the sun is still above the horizon. OIF UMSU as an institution engaged in the field of falak science also conducts crescent observations every month from noon. On November 25, 2022, OIF Barus Team managed to capture the new moon crescent at noon at 13:49 WIB with an elongation of 18°25'. This observation could maximizing existing instruments to obtain crescent images with smaller elongation.